Dibrey Hephez, |``Acceptable words'' or extract from various unprinted works of eminent hebrew authors [...] in four parts (Shaw Abraham Pierpoint, 1853)
Auf S. 6 steht ein Schachgedicht von Salomo ben Massaltab
st. zas. Os.
Keywords: szachy